Correlation between the Constitution of Sasang and Sexual Difference in the Hypersensitive Reaction of Sweet Bee Venom - Lee Kwangho (Korean Pharmacopuncture Institute, 2012)
Objectives: The aim of this study is to investigate the correlation between the constitution of Sasang and the bee venom hypersensitive reaction, as well as the hypersensitive reaction occurrence ratio between males and females, for patients treated with sweet bee venom (SBV) and who had undergone an examination of the constitution of the Sasang. Methods: All 81 patients enrolled in the study were treated with SBV and underwent an examination of the constitution of Sasang from January 2010 to July 2012. We divided them into two groups for the hypersensitive reaction and no response and compared the distributions of the Sasang-constitution types for the two groups as well as the hypersensitive reaction occurrence ratio between males and females. Results: No significant differences were found between the hypersensitive-reaction group and the no-response group (p = 0.390), but the hypersensitive-reaction occurrence ratio was statistically higher in females than in males (p = 0.001). Conclusions: Hypersensitive reactions do not seem to be related to the Sasang-constitution types, but the possibility of hypersensitive reactions among females seems to be higher than it is among males.